2019
DOI: 10.1097/md.0000000000014884
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusion threshold after pediatric cardiac surgery

Abstract: Background:Restrictive red blood cell transfusion strategy is implemented to minimize risk following allogeneic blood transfusion in adult cardiac surgery. However, it is still unclear if it can be applied to pediatric cardiac patients. The purpose of this systematic review and meta-analysis was to determine the effect of postoperative restrictive transfusion thresholds on clinical outcomes based on up-to-date results of randomized controlled trials (RCTs) and observational studies in pediatric cardiac surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A previous meta-analysis of four studies suggested that a restrictive transfusion strategy is non-inferior to a liberal transfusion strategy in pediatric cardiac surgery [13]. However, this study has a limitation.…”
Section: Introductionmentioning
confidence: 76%
“…A previous meta-analysis of four studies suggested that a restrictive transfusion strategy is non-inferior to a liberal transfusion strategy in pediatric cardiac surgery [13]. However, this study has a limitation.…”
Section: Introductionmentioning
confidence: 76%
“…10,14,15 However, two subsequent meta-analyses comparing "restrictive" and "liberal" packed red blood cell transfusion strategies during paediatric cardiac surgery found no significant difference in risk of in-hospital mortality, infection, blood loss, duration of mechanical ventilation, or length of stay. 16,17 Furthermore, subgroup analysis of patients with cyanotic CHD treated with "liberal" transfusion strategy demonstrated a significantly shorter duration of post-operative mechanical ventilation. 16 Regarding efficacy, outcome measures focusing on oxygen delivery biomarkers such as lactate and mixed venous oxygen saturation (SvO 2 ) have failed to find consistent benefit from packed red blood cell transfusion transfusion after paediatric cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…To counteract possible negative consequences of severe anemia for infants following surgery of congenital heart disease, red blood cell (RBC) transfusions are commonly administered to replace blood loss with the intention to optimize oxygen delivery or to achieve favorable hemodynamic conditions [5,7]. However, there is an increasing number of studies showing negative impact of RBC transfusions on PICU stay, length of mechanical ventilation, postoperative infections, organ dysfunction, and mortality [3,4,8,10,13,23,26].…”
Section: Introductionmentioning
confidence: 99%